Disiplin Kerja dan Stres Kerja pada Kinerja Karyawan PAM Tirta Karajae - Sampe, Bernadeti Inchi; D'Ornay, Anastasia; Rifani, Riza Amalia (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
The aims of this study are: (1) To find out the variables of discipline and work stress partially affect the performance of employees at the Public Drinking Water Company (PAM) Tirta Karajae, Parepare City. (2) To find out the variables of discipline and work stress simultaneously affect the performance of employees at the Drinking Water Company (PAM) Tirta Karajae, Parepare City. In this study the analysis used was validity test, reliability test, multiple linear regression, partial test (t-test), simultaneous test (F test) and the coefficient of determination (R2) to determine the existing hypothesis in this study, the samples used in this study were employees at PAM Tirta Karajae Parepare City as many as 51 employees. Work discipline variable (X1) has a partial effect on the performance of employees (Y) of PAM Tirta Karajae, Parepare City. This is evidenced by the significant value of 0.005 2.010). The work stress variable (X2) has no partial effect on employee performance (Y) with a significant value of 0.424 > 0.05 and (0.807 < 2.010). Based on the test results on work discipline and work stress it was found that 17.521 > 2.71 and a significant level of 0.000